2018
DOI: 10.3390/nu10121990
|View full text |Cite
|
Sign up to set email alerts
|

Per-Arnt-Sim Kinase (PASK) Deficiency Increases Cellular Respiration on a Standard Diet and Decreases Liver Triglyceride Accumulation on a Western High-Fat High-Sugar Diet

Abstract: Diabetes and the related disease metabolic syndrome are epidemic in the United States, in part due to a shift in diet and decrease in physical exercise. PAS kinase is a sensory protein kinase associated with many of the phenotypes of these diseases, including hepatic triglyceride accumulation and metabolic dysregulation in male mice placed on a high-fat diet. Herein we provide the first characterization of the effects of western diet (high-fat high-sugar, HFHS) on Per-Arnt-Sim kinase mice (PASK−/−) and the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 56 publications
3
13
0
Order By: Relevance
“…In contrast, female mice displayed no significant increase in GFP on the HFHS diet, but PASK-deficient females displayed a twofold increase in RFP on the HFHS diet, relative to PASK-NCD or WT-NCD controls (p = 0.0042 and 0.0141, respectively, Figure 1C). This observation of significant differences in the body weight at certain time points, and the final RFP weight, is the first report of what appears to be dyslipidemia in the female PASK-deficient mice, which have generally shown no reported PASK −/− phenotype, including no observable difference in liver triglycerides [31]. The relative weights (tissue weight/final body weight) of male retroperitoneal fat pads (RFP) (WT p = 0.0029, PASK p = 0.0002) and gonadal fat pads (GFP) (WT p = 0.0608, PASK p = 0.0141) also displayed differences relative to their NCD genotype controls, due to an interaction between the diet and genotype (Figure 1C).…”
Section: Pask −/− Deletion Does Not Protect Against Weight Gain On An Hfhs Diet But Does Protect Against Hepatic Triglyceride Accumulatiomentioning
confidence: 61%
See 1 more Smart Citation
“…In contrast, female mice displayed no significant increase in GFP on the HFHS diet, but PASK-deficient females displayed a twofold increase in RFP on the HFHS diet, relative to PASK-NCD or WT-NCD controls (p = 0.0042 and 0.0141, respectively, Figure 1C). This observation of significant differences in the body weight at certain time points, and the final RFP weight, is the first report of what appears to be dyslipidemia in the female PASK-deficient mice, which have generally shown no reported PASK −/− phenotype, including no observable difference in liver triglycerides [31]. The relative weights (tissue weight/final body weight) of male retroperitoneal fat pads (RFP) (WT p = 0.0029, PASK p = 0.0002) and gonadal fat pads (GFP) (WT p = 0.0608, PASK p = 0.0141) also displayed differences relative to their NCD genotype controls, due to an interaction between the diet and genotype (Figure 1C).…”
Section: Pask −/− Deletion Does Not Protect Against Weight Gain On An Hfhs Diet But Does Protect Against Hepatic Triglyceride Accumulatiomentioning
confidence: 61%
“…Despite the lack of protection against body weight gain or liver weight reduction by PAS kinase deficiency, male PASK-HFHS mice were protected from liver triglyceride accumulation in response to the HFHS diet, while WT mice displayed elevated triglycerides relative to the WT-NCD control (p = 0.0234) (Figure 1E, p = 0.0592 between PASK and WT HFHS). We previously reported this protection from triglyceride accumulation of male, but not female, mice in a study of mice from this same cohort [31]. Due to the dramatic body weight gain and liver triglyceride accumulation phenotype in male mice, as well as the previous report of male-specific phenotypes [28,31], male mice were the focus of the remainder of this study.…”
Section: Pask −/− Deletion Does Not Protect Against Weight Gain On An Hfhs Diet But Does Protect Against Hepatic Triglyceride Accumulatiomentioning
confidence: 75%
“…These results are consistent with the present findings. Other studies in mammals reported that PSK kinase deficiency is associated with relative decrease in insulin production, insulin resistance, triglyceride accumulation, and protects against high fat‐diet‐induced obesity (Cardon & Rutter, ; Hao et al, ; Hurtado‐Carneiro et al, ; Pape et al, ). Our results do not only provide an insight into the mechanism of biological rhythms but are also potentially useful for the design of new treatments for human metabolic syndrome and/or diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In hSOD1 G93A mice, exercise was beneficial for females only 83 . Male/female wild‐type mice show dramatic differences in response to a high‐fat diet, 84 suggesting this diet may behave differently in ALS mice. Thus, in our further studies involving ALS, both males and females will be included, with sex being an additional variable analysed statistically.…”
Section: Discussionmentioning
confidence: 99%